Toward simplified oral lipid-based drug delivery using mono-/di-glycerides as single component excipients. (1st December 2020) - Ilie, Alexandra-Roxana; Griffin, Brendan T.; Vertzoni, Maria; Kuentz, Martin; Cuyckens, Filip; Wuyts, Koen; Kolakovic, Ruzica; Holm, René
Abstract: Objective: This study aimed to systematically explore compositional effects for a series of lipid systems, on the in vitro drug solubilization and in vivo bioavailability of three poorly water-soluble drugs with different physico-chemical properties. Significance: While many lipid-based drug products have successfully reached the market, there is still a level of uncertainty on the design guidelines for such drug products with limited understanding on the influence of composition on in vitro and in vivo performance. Methods and Results: Lipid-based drug delivery systems were prepared using either single excipient systems based on partially digested triglycerides (i.e. mono- and/or di-glycerides) or increasingly complex systems by incorporating surfactants and/or triglycerides. These lipid systems were evaluated for both in vitro and in vivo behavior. Results indicated that simple single component long chain lipid systems are more beneficial for the absorption of the weak acid celecoxib and the weak base cinnarizine compared to equivalent single component medium chain lipid systems. Similarly, a two-component system produced by incorporating small amount of hydrophilic surfactant yields similar overall pharmacokinetic effects. The lipid drug delivery systems based on medium chain lipid excipients improved the in vivo exposure of the neutral drug JNJ-2A. The higher in vivo bioavailability of long chain lipid systems compared to medium chain lipid systems was in agreement with in vitro dilution and dispersion studies for celecoxib and cinnarizine. Conclusions: The present study demonstrated the benefits of using mono-/di-glycerides as single component excipients in LBDDS to streamline formulation screening and improve oral bioavailability for the three tested poorly water-soluble drugs.